Kapitał zagraniczny w gminie Wrocław w ujęciu sektorowym - Polak, Waldemar (Foreign Capital in the Wrocław Commune - Sector Approach, 2007)
The scope of the paper is an analysis and assessment of foreign capital investments level in Ее commune of Wrocław in a sectoral approach for the period till 30th June 2005. changes in the Polish economy observed in the beginning of 1990s (especially these concerning economic legislation and institutional transformations) created good conditions for foreign investors. They allocated their resources in a form of foreign direct investment (FDI) in Poland, including Lower Silesia. Reasons for this are as follows: geographical location of the district, economic capacity of entities operating in this area and investment opportunities created by the city and commune of Wrocław.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 419-430